Analisis Karakteristik Curah Hujan pada Kawasan Hunian dan Komersial Pantai Indah Kapuk (PIK) 2 Cluster “C” - Nur Afifah Sari; Etih Hartati; M. Candra Nugraha (Fakultas Teknik, 2020)
Based on the hydrological cycle, one of the main water sources is rainwater. weather or climate conditions that occur will greatly affect the nature and condition of a rain or rainy season. On a global scale, the existence of water naturally is constant, only occurs in variations both in time and space on a regional scale. Analysis of the rainfall characteristics of Pantai Indah Kapuk (PIK) residential and commercial areas 2 Cluster